Speculative price bubbles in urban housing markets - Konstantin A. Kholodilin; Claus Michelsen; Dirk Ulbricht (Empirical Economics, 2018)
In the light of the unconventional monetary policies implemented by most large central banks around the world, there is an intense debate about the potential impact on the prices of capital assets. Particularly in Germany, skepticism about the sustainability of the current policy by the European Central Bank is wide spread and concerns about the emergence of a speculative price bubble in the housing market are increasing. The present study analyzes a comprehensive data set covering 127 large German cities from 1990 through 2013, using tests for speculative bubbles, both at a national and city level. Furthermore, we apply two new testing approaches: panel-data and principal components versions of explosive root tests. We find evidence for explosive price increases in many cities. However, it is only in select urban housing markets that prices decouple from their fundamental values. There is no evidence for speculative price movements nationally.
Keywords: C21; C23; C53; 330; housing prices; speculative bubble; explosive root; german cities